Enabling Digital Transformation Success: The Roles of Organizational Agility, IT Flexibility, and Dynamic Capabilities - Weber, Ploychompoo; Peemanee, Jindarat; Issarapaibool, Achariya; Siriyota, Kampanat (International Review of Management and Marketing, 2026)
This study examines how dynamic capabilities (sensing, seizing, and reconfiguring) and IT infrastructure flexibility enhance organizational agility and digital transformation success. Drawing on the dynamic capabilities view; a mediated model is proposed in which organizational agility links capabilities to transformation outcomes. Data were collected from 446 respondents in Thai digital enterprises and analyzed using PLS-SEM with Smart PLS 4.0. The results show that sensing capability has the strongest effect on organizational agility, followed by IT infrastructure flexibility, while seizing and reconfiguring capabilities have smaller but significant effects. Organizational agility significantly enhances digital transformation success and mediates the effects of capabilities and IT flexibility on performance. These findings highlight agility as a key mechanism through which organizational capabilities support successful digital transformation.